Slow‐slip events on the Whillans Ice Plain, Antarctica, described using rate‐and‐state friction as an ice stream sliding law. Issue 4 (21st April 2017) - Lipovsky, Bradley Paul; Dunham, Eric M.
Abstract : The Whillans Ice Plain (WIP), Antarctica, experiences twice daily tidally modulated stick‐slip cycles. Slip events last about 30 min, have sliding velocities as high as ∼0.5 mm/s (15 km/yr), and have total slip ∼0.5 m. Slip events tend to occur during falling ocean tide: just after high tide and just before low tide. To reproduce these characteristics, we use rate‐and‐state friction, which is commonly used to simulate tectonic faulting, as an ice stream sliding law. This framework describes the evolving strength of the ice‐bed interface throughout stick‐slip cycles. We present simulations that resolve the cross‐stream dimension using a depth‐integrated treatment of an elastic ice layer loaded by tides and steady ice inflow. Steady sliding with rate‐weakening friction is conditionally stable with steady sliding occurring for sufficiently narrow ice streams relative to a nucleation length. Stick‐slip cycles occur when the ice stream is wider than the nucleation length or, equivalently, when effective pressures exceed a critical value. Ice streams barely wider than the nucleation length experience slow‐slip events, and our simulations suggest that the WIP is in this slow‐slip regime. Slip events on the WIP show a sense of propagation, and we reproduce this behavior by introducing a rate‐strengthening region in the center of the otherwise rate‐weakening ice stream. If pore pressures are raised above a critical value, our simulations predict that the WIP would exhibit quasi‐steady tidally modulated sliding as observed on other ice streams. This study validates rate‐and‐state friction as a sliding law to describe ice stream sliding styles. Plain Language Summary: The Whillans Ice Plain, a 120 km wide region of the West Antarctic Ice Sheet, experiences slip events that bear similarity to tectonic earthquakes. During a slip event, the entire 120 km region slides forward by about half a meter over a period of about 30 min. Remarkably, on most days these slip events occur just after high tide and just before low tide. These slip events are much slower and have much lower ground accelerations than typical tectonic earthquakes of this size. We create computer simulations of these slip events using a type of friction law originally discovered in the study of tectonic earthquake. We show that the slow‐slip events on the Whillans Ice Plain are similar to slow‐slip events in subduction zones in that they nucleate over very long distances. Our model also recreates the general type of behavior observed in other parts of Antarctica where slip events do not occur. By better describing the friction at the base of the ice sheet, we hope to improve the computer simulations of ice sheet dynamics that constrain estimates of future sea level rise. Key Points: We validate a laboratory‐derived sliding law, rate‐and‐state friction, as an ice stream basal sliding law Stick‐slip cycles on the Whillans Ice Plain, West Antarctica, occur in the slow‐slip limit of sliding behavior Rate‐and‐state friction captures the transition between tidally modulated stick‐slip motion and quasi‐steady tidal modulation